Power and Privilege: Investigating Sexual Violence with Digital Open Source Information. (17th May 2021) - Koenig, Alexa; Egan, Ulic
Abstract: Digital open source information — including the videos and photographs that people post to social media and other publicly accessible platforms — is increasingly valued as a critical source of evidence. While investigators have repeatedly established the value of open source information for researching a range of crimes, there is a subset of crimes that investigators have struggled to address with digital open sources — namely, sexual violence. In this article, we report on findings pulled from our interviews with international investigators and gender experts with regards to the perceived strengths and weaknesses of integrating digital open source information into international criminal investigations of sexual violence. More specifically, we elaborate on three insights into how open source investigations may be refined to better respect and protect the interests of survivors: by considering contextual issues related to ethics, power, and privilege, including the identity of the investigator and of the victims; by integrating a gender analysis and an intersectional analysis into online investigation planning; and by being thoughtful about consent, privacy, trauma and control — including who determines what happens with open source information and how such information is used in courts. We conclude with a discussion of what is needed to strengthen the efficacy and ethics of sexual violence investigations through the use of digital open sources.